Methods for calculating the severity of demineralization on tooth surfaces from PS-OCT scans - Le, Michael H. (2009)
Several studies have demonstrated that polarization sensitive optical coherence tomography (PS-OCT) can be used to nondestructively measure the severity of subsurface demineralization in enamel and dentin. The reflectivity in the polarization state orthogonal to the initial linear polarization incident on the tissue is low at sound tissues interfaces and high in demineralized areas that strongly scatter and depolarize the light. The purpose of this study was to develop improved algorithms for assessing the depth and severity of demineralization from PS-OCT scans for use with 2D and 3D tomographic images. Subsurface caries-like lesions of increasing depth and severity were produced in adjoining windows on ten bovine enamel samples by exposure to demineralization over periods of 1 to 4 days. Each sample also had a sound window to be used as a control. PS-OCT scans were acquired for each sample and analyzed using various methods to calculate the lesion depth and area. Algorithms were developed and used to automatically detect the lesion depth and area, and calculate the volume for improved assessment of lesion severity. Both fixed-depth and automatic edge-finding algorithms were able to detect significant differences between each of the days and sound enamel. The lesion depth and mineral loss were also measured with polarized light microscopy and transverse microradiography after sectioning the teeth. Mean lesion depths ranged from 40 to 100 μm. This demonstrates the edge-finding algorithm can be used to automatically determine the depth and severity of early lesions for the rapid analysis of PS-OCT images.